Empathetic Reflections on Love, Life, and Death Art in Othello - Tooker, Jessica (The Shakespearean Death Arts, 2022)
Requesting that Desdemona safeguard his first love gift (the infamous handkerchief), Othello highlights the remarkable properties of the object as a narrative device. "There’s magic in the web of it," (3.4.71) he explains to his wife. Demonstrating that he won Desdemona’s love with words, Othello enjoins the audience’s empathy with his devotion to her. A stunning reversal of another linguistic technique in the play—what I would call "wounding words," or hate speech which affectively, even traumatically impacts the audience—Othello’s narrative showcases how the couple’s relationship infuses the present moment with a potent life force serving as a ballast against inexorable mortality. Of course, the onus of this rhetorically curative work also falls upon the offstage audience, whose empathetic witnessing of the couple’s passionate relationship—spoken of by themselves and others using feeling and aestheticized language—undoes the scarring damage done by injurious speech. To be sure, in Shakespeare’s Othello the forces of life and death are hypnotically, and often verbally juxtaposed, as when, for example, Othello strikingly recounts his marvelous foreign travels for the Venetian senate and the audience, thus establishing himself as both an exotic "Other" and the man whose words and deeds compellingly bespeak his humanness. Interrogating the "death art" of performative language, or what might be called "thana-rhetoric," deployed as an affective mechanism simultaneously signaling a consciousness of mortality and invoking a form of transcendent humanity, my essay analyzes the play’s artful obsession with words as signifiers of not only love (and its fatal counterpart, hate)—but human life as it would, with downright violence, confront the specter of death.